2007
DOI: 10.1123/tsp.21.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Flow Experience and Athletes’ Performance with Reference to the Orthogonal Model of Flow

Abstract: The purposes of the current study were to examine (a) the differences in Flow State Scale (FSS) subscales between the 4 experiential states of the orthogonal model (apathy, anxiety, relaxation, and flow), (b) the relationship between challenge, skills, and flow experience; and (c) the relationship between flow experience and athletes’ performance. Two hundred twenty athletes volunteered to participate in this study. Challenge of the game and skills of the athlete were measured before and after competition. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 33 publications
4
62
1
1
Order By: Relevance
“…Similarly, significant relations have been found between strengths use and subjective vitality Govindji and Linley 2007;Wood et al 2011), while subjective vitality has been associated with well-being (Ryan and Frederick 1997) and work performance (Carmeli et al 2009;Salanova et al 2005). Likewise, strengths have also been shown to predict flow and absorption through the engaged life orientation to happiness (Buschor et al 2013;Peterson et al 2007), while flow has been associated to well-being (Fritz and Avsec 2007;Wanner et al 2006) and performance at work (Demerouti 2006;Eisenberger et al 2005;Kuo and Ho 2010), in sports (Bakker et al 2011;Schuler and Brunner 2009;Stavrou et al 2007) and academic settings (Engeser and Rheinberg 2008). More recently, research has further confirmed the plausibility of this general model, as strengths use was associated with work performance through the pathways of harmonious passion, subjective vitality and concentration (Dubreuil et al 2014).…”
Section: Strengths Use and Possible Underlying Processesmentioning
confidence: 99%
“…Similarly, significant relations have been found between strengths use and subjective vitality Govindji and Linley 2007;Wood et al 2011), while subjective vitality has been associated with well-being (Ryan and Frederick 1997) and work performance (Carmeli et al 2009;Salanova et al 2005). Likewise, strengths have also been shown to predict flow and absorption through the engaged life orientation to happiness (Buschor et al 2013;Peterson et al 2007), while flow has been associated to well-being (Fritz and Avsec 2007;Wanner et al 2006) and performance at work (Demerouti 2006;Eisenberger et al 2005;Kuo and Ho 2010), in sports (Bakker et al 2011;Schuler and Brunner 2009;Stavrou et al 2007) and academic settings (Engeser and Rheinberg 2008). More recently, research has further confirmed the plausibility of this general model, as strengths use was associated with work performance through the pathways of harmonious passion, subjective vitality and concentration (Dubreuil et al 2014).…”
Section: Strengths Use and Possible Underlying Processesmentioning
confidence: 99%
“…Apart from studying flow experience for its own sake, research in human-computer interaction has used non-experimental designs -with consequent threats to internal validity -to study flow experience mainly in relation to its influence on social-cognition variables such as evaluative judgments in the form of attitudes (Agarwal and Karahanna, 2000) and behavioural outcomes (Koufaris, 2002). However, although it has been demonstrated that flow experience is an independent positive predictor of task outcome (after controlling for other [cognitive] variables) in the domains of sport (Stavrou et al, 2007), education (Engeser and Rheinberg, 2008;Vollmeyer and Imhof, 2007), and computer-game playing (Engeser and Rheinberg;Vollmeyer and Rheinberg, 2003;Murphy et al, 2008), there is a lack of research in human-computer interaction studying flow in relation to cognitive-task outcomes.…”
Section: Dimension Descriptionmentioning
confidence: 97%
“…Flow experience has been studied in many domains such as sport (Stavrou et al, 2007), education (Engeser and Rheinberg, 2008), computer gaming (Murphy et al, 2008) and human-computer interaction (e.g., Pace, 2004;van Schaik and Ling (2007)). Nine dimensions of flow (see Table 1) have been distinguished (Csikszentmihalyi, 1988) and measurement instruments for these dimensions have been developed and validated (e.g., Jackson and Marsh, 1996;Jackson and Eklund, 2002).…”
Section: Experience and Task Performancementioning
confidence: 99%
“…The flow state is achieved when all contents of consciousness are in harmony with each other and with the objectives set by the person to perform a certain task (Csikszentmihalyi & Csikszentmihalyi, 1988). Studies have shown that situational and personal characteristics affect the quality of experience (Stavrou, Zervas, Karteroliotis, & Jackson, 2007), in particular, because the flow state is related to the perception that the individual have of the existing challenges in the task and the perception of his personal skills (Csikszentmihalyi, 1990).…”
Section: Flow Predisposition In Rugby | 19mentioning
confidence: 99%
“…However, the factors determining the flow experience could be distinct in different sports contexts (Jackson, Kimiecik, Ford, & Marsh, 1998;Young & Pain, 1999). The challenges of competition and athlete's skills are two subjective variables that may have a dependent or an independent effect on the quality of experience (Stavrou et al, 2007), because, before or during the competition, the level of challenge and skill are dynamic in nature, depending on individual quality (time of experience, mental preparation, physical preparation) or situational characteristics (the importance of competition, the opponent, etc.). In this sense, some aspects are crucial and were pointed out by athletes of competitive level sports as facilitators for the flow experience.…”
Section: Flow Predisposition In Rugby | 19mentioning
confidence: 99%